Understanding Educator Attitudes Toward the Implementation of Inclusive Education - Subban, Pearl; Sharma, Umesh (Disability Studies Quarterly, 2005)
This paper presents the findings of an empirical study to investigate the attitudes of regular education teachers toward the implementation of inclusive education. The cited study was part of a two-pronged research inquiry which investigated teachers attitudes toward, and their concerns about inclusive education. This discourse was based on semi-structured interviews, conducted with mainstream teachers in state schools in Victoria, Australia. The results imply that Victorian teachers are in the main positively inclined towards the philosophy of inclusive education, perceiving the process as beneficial to all participants within the inclusive setting. However, they remain cautious about the inclusion of students with more severe disabilities.